Strengthening Public Financial Management in Postconflict Countries - Fritz, Verena; Hedger, Edward; Fialho Lopes, Ana Paula (World Bank, Washington, DC, 2012)
Understanding how to rebuild resilient states in post-conflict countries is an urgent priority for the international community. A new cross-country study of public financial management reforms in post-conflict situations shows that substantial progress is possible even in difficult circumstances, while showing a pattern of sequencing and progress that differs from standard assumptions. However, the impact on state building remains less than what might be hoped. That impact could be strengthened by persistently targeting sustainable capacity, challenging areas such as procurement, greater public awareness, and more rapid coverage of line ministries and sub-national levels.